2005
DOI: 10.1038/nature03434
|View full text |Cite
|
Sign up to set email alerts
|

Loss of cyclophilin D reveals a critical role for mitochondrial permeability transition in cell death

Abstract: Mitochondria play a critical role in mediating both apoptotic and necrotic cell death. The mitochondrial permeability transition (mPT) leads to mitochondrial swelling, outer membrane rupture and the release of apoptotic mediators. The mPT pore is thought to consist of the adenine nucleotide translocator, a voltage-dependent anion channel, and cyclophilin D (the Ppif gene product), a prolyl isomerase located within the mitochondrial matrix. Here we generated mice lacking Ppif and mice overexpressing cyclophilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

86
1,961
6
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,020 publications
(2,104 citation statements)
references
References 26 publications
86
1,961
6
13
Order By: Relevance
“…Hepatocyte mitochondria from control and Ppif À/À mice exhibited identical cyt c release patterns when treated with recombinant Bax or t-Bid (truncated Bid) proteins, whereas Ppif À/À mitochondria were protected from Ca 2 þ -induced cyt c release (Baines et al, 2005;Nakagawa et al, 2005). This indicates that the MOMP induced by proapoptotic Bcl-2 family members can occur independently from CypDregulated events.…”
Section: Mitochondrial Membrane Permeabilization: the Central Event Omentioning
confidence: 94%
“…Hepatocyte mitochondria from control and Ppif À/À mice exhibited identical cyt c release patterns when treated with recombinant Bax or t-Bid (truncated Bid) proteins, whereas Ppif À/À mitochondria were protected from Ca 2 þ -induced cyt c release (Baines et al, 2005;Nakagawa et al, 2005). This indicates that the MOMP induced by proapoptotic Bcl-2 family members can occur independently from CypDregulated events.…”
Section: Mitochondrial Membrane Permeabilization: the Central Event Omentioning
confidence: 94%
“…Indeed, it was demonstrated that mPTP formation and apoptotic cell death could still occur in the absence of either ANT [57] or VDAC [58]. In contrast, overexpression of CyPD induced mitochondrial swelling and spontaneous cardiac apoptosis, whereas mice lacking cardiac CyPD were protected from ischemia/reperfusion-induced cell death [59]. Once MOMP has occurred, the release of apoptogenic factors stored in the mitochondrial intermembrane space ensues, initiating the series of events that culminate in cell death [31].…”
Section: The Involvement Of Apoptosis In the Pathogenesis Of Sarcopeniamentioning
confidence: 99%
“…Currently, a common agreement considers that cyclophilin D (CypD), a soluble protein located within the mitochondrial matrix, is the main partner of the mPTP (Gutiérrez‐Aguilar & Baines, 2015) and that mPTP formation is greatly sensitized by CypD which lowers the calcium threshold required to trigger mPTP opening. The crucial role of CypD has been shown by deletion of the gene in mice, allowing mitochondria to sustain high calcium concentrations and thus conferring major desensitization of mPTP (Baines et al., 2005). Two opening states of the pore have been distinguished, a permanent or long‐lasting state which is associated with cell death, and a transient opening state having a physiological role by providing a pathway to release ROS and calcium from mitochondria which is also regulated by CypD (Elrod et al., 2010; Hausenloy, Wynne, Duchen, & Yellon, 2004; Petronilli et al., 1999).…”
Section: Introductionmentioning
confidence: 99%